1996
DOI: 10.1093/infdis/173.5.1256
|View full text |Cite
|
Sign up to set email alerts
|

The Seroepidemiology of Bordetella pertussis Infections: A Study of Persons Ages 1-65 Years

Abstract: Although the incidence of Bordetella pertussis infections had decreased significantly since the introduction of widespread vaccination, an increase in the number of cases has occurred recently. In an attempt to define the seroepidemiology of pertussis in Nashville, antibody levels to pertussis toxin (PT) and filamentous hemagglutinin (FHA) were measured by ELISA in 585 serum samples from healthy 1- to 65-year-old subjects. Data were analyzed by smooth curve fitting and by comparison of trends in PT and FHA tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 12 publications
7
65
1
3
Order By: Relevance
“…12 Data from a seroprevalence study by Cattaneo et al showed a peak in antibody titers at 4 to 6 years of age, coinciding with DTaP booster dosing, followed by a decline, and a second peak between 13 and 17 years of age. 13 Similar findings were documented by the National Health and Nutrition Examination Survey (NHANES), which reported a protracted decline interrupted by a peak in persons aged 40 to 45 years.…”
supporting
confidence: 72%
“…12 Data from a seroprevalence study by Cattaneo et al showed a peak in antibody titers at 4 to 6 years of age, coinciding with DTaP booster dosing, followed by a decline, and a second peak between 13 and 17 years of age. 13 Similar findings were documented by the National Health and Nutrition Examination Survey (NHANES), which reported a protracted decline interrupted by a peak in persons aged 40 to 45 years.…”
supporting
confidence: 72%
“…1), the group with a lower seroprevalence for B. pertussis consists of subjects between 30 and 34 y of age followed by an increase in those 35-39 y. This increase could be related to differences in the kinetics of PT 36 or to the waning immune response observed 10 to 20 y after natural infection potentially occurring during adolescence, once protection of primary vaccination was lost. 37 The 25 to 29 age group displayed the highest seroprevalence figures.…”
Section: Studymentioning
confidence: 99%
“…These data coincide with that described in several studies conducted in other countries. [36][37][38] As value and negative when absorbance values were less than 15% of the cut-off value. Statistical analysis.…”
Section: Studymentioning
confidence: 99%
“…Las razones para el insuficiente control de la enfermedad son varias y complejas e incluyen por un lado la duración limitada de la protección que otorgan las vacunas www.sochinf.cl que va de 4 a 12 años según diferentes estudios 3, [8][9][10] , así como su incapacidad para interrumpir la circulación de Bordetella pertussis 11,12 dado su escaso efecto en portación nasofaríngea del agente. Así mismo, es probable que la presión selectiva que ejercen las vacunas, esté favoreciendo la emergencia de cepas mutantes del microorganismo, con mejores mecanismos patogénicos que logren infectar a individuos vacunados [13][14][15][16] .…”
Section: Causas De Los Brotesunclassified